Social factors affecting women's tendency to body management in Qom - A. Babaiefard; T. Yoosefifar; Z. Amjadi (Taḥqīqāt-i Farhangī-i Īrān)
The present study aimed to investigate the effect of social factors on women’s Body Management in Qom. The theoretical framework was based on various theories by Giddens, Goffman, Nan Lane, Cooley, and Homans. This study was based on a survey design, and the data were collected by a researcher-made questionnaire. The statistical population included all women aged 16-60 years old in Qom. A total of 384 participants were selected using the Cochran’s Formula and quota sampling. SPSS software (Version 22) was used for data analysis. The findings indicated that body management had a significant and direct relationship with social pressure, social acceptance, and life satisfaction as well as achieving a higher social status and attracting the opposite sex. In addition, the results of regression analysis revealed that the aforementioned variables could explain 41% of the changes in ‘Body Management’. Furthermore, implications of the findings for social policy making were discussed. Finally, some suggestions were made for dealing with extreme tendency towards Body Management.